Hubungan Pemakaian Inhalasi Kortikosteroid Flutikason Dengan Kejadian Eksaserbasi Pada Pasien Penyakit Paru Obstruksi Kronik Di Rumah Sakit Umum Daerah Abdul Moeloek Provinsi Lampung Periode Tahun 2015-2017 - Novita Carolia; Anggraeni Janar Wulan; Natasya Aurum Alifia Zaini (CV. Jasa Sukses Abadi, 2020)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic lung disease with irreversible condition. One of the treatmentusing fluticasone inhaled corticosteroids shows a significant improvement in lung function, reducing symptoms andreducing exacerbations. The purpose of this study was to determine the relationship of fluticasone corticosteroid inhalationwith the incidence of exacerbations in COPD patients at Abdul Moeloek Regional Hospital in the period 2015-2017 LampungProvince. This study was an observational study that used secondary data (medical records) of 102 patients who wereanalyzed the type of the drug they used with the occurrence of exacerbations they experienced. The results of the analysisin this study showed a significant correlation between the use of fluticasone inhaled corticosteroids and the exacerbationsin COPD patients at Abdul Moeloek Hospital in 2015-2017 with a p value of 0.049 (p <0.05).